Measuring the soil compaction zone and pressure of deformed soil on underground objects with an asymmetric cylindrical tip - Suponyev, V. M.; Fidrovska, N. M.; Balesnyi, S. P.; Ragulin, V. M.; Kravets, S. V.; Супонєв, В. М.; Фідровська, Н. М.; Балесний, С. П.; Рагулін, В. М.; Кравець, С. В. (Харківський національний автомобільно-дорожній університет, 2021)
At trenchless laying of engineering communications in soil the method of static puncture has received wide application at formation of a well. Power plants that implement it have small di-mensions, which make them more effective in laying distribution engineering networks in tight urban conditions. Problem. The main disadvantages of the method are the low accuracy of the trajectory and the significant stress in the soil after its compaction, which can lead to the de-struction of adjacent underground objects. The first disadvantage is solved by controlling the trajectory of the soil-piercing working body. To solve the second question, it is necessary to know and take into account the specifics of the formation of communication cavities in the soil with an asymmetric tip, which is used for this purpose. Goal. The aim of the work is to establish the regularity of the process of soil puncture by the soil-piercing working body with an asym-metric tip in the form of a cylinder cut at an angle. Methodology. The approaches adopted in the work to solve this goal are based on the theories of deep soil cutting, scientific foundations of soil mechanics, their normative physical and mechanical properties and the law of conserva-tion of soil mass before and after compaction. Results. The calculated dependences for deter-mining the size of the destructive zone from the elastic-plastic deformation of the soil during its puncture by an asymmetric tip with a frontal surface in the form of a beveled cylinder and the pressure of the deformed soil on underground objects are obtained. It is established that the maximum size of the destruction zone and its pressure on underground objects will occur in sol-id sand. With a tip diameter of 0.3 m, their values can reach 5 m and 0.245 MPa, respectively. Originality. The obtained regularities of soil puncture by a working body with an asymmetric tip in the form of a beveled cylinder made it possible to get an idea of the influence of its deformed state on adjacent communications depending on geometric parameters of the tip and physical and mechanical properties of soils. Practical value. The obtained results can be recommended in the design and determination of technological capabilities of installations for static soil punc-ture.
Визначення величини зони ущільнення ґрунту та тиску деформованого ґрунту на підземні об’єкти асиметричним циліндричним наконечником
Keywords: trenchless technologies; soil puncture; soil compaction; engineering communications; horizontal well; communication cavity; безтраншейні технології; прокол ґрунту; ущільнення ґрунту; інженерні комунікації; горизонтальна свердловина; комунікаційна порожнина; 624.132.3; 10.30977/AT.2219-8342.2021.48.0.93